(untitled) (Applied Biological Research, 2015)
A study on the prevalence of intestinal helminth infections, using stool samples of 396 school children comprising of 198 each male and female randomly selected from 50 households, was conducted in Elele, South South Nigeria, between March and June, 2013. Their basic information like sex, age and drinking water source were collected using a self administered questionnaire. The prevalence of intestinal helminth infection varied significantly among males (6.57%) and females (3.4%). Prevalence also varied significantly among various age groups, with age group 7-9 having highest infection of Trichuris trichiura (2.25%) while age group 4-6 had higher prevalence of Strongyloides stercoralis and Taenia sp. (1.65%). Children within age group 1-3 years had highest prevalence of Ascaris lumbricoides (2.38%) and finally children within age group 10-12 were with the highest prevalence rate of hookworm (1.96%). Similarly the people who drink stream water had higher prevalence values i.e. 2.27, 3.03, 3.03 and 1.52% for S. stercoralis, A. lumbricoides, Taenia sp. and hookworms, respectively. T. trichiura was absent in people who drink stream water while those who drink Sachet or table water had prevalence rate of 1.52%.